2021
DOI: 10.1038/s41598-021-93939-6
|View full text |Cite
|
Sign up to set email alerts
|

Control of stripe rust of wheat using indigenous endophytic bacteria at seedling and adult plant stage

Abstract: Stripe rust (caused by Puccinia striiformis tritici) is one of the most devastating diseases of wheat. The most effective ways to control stripe rust are the use of resistant cultivars and the timely use of an appropriate dose of fungicide. However, the changing nature of rust pathogen outwits the use of resistant cultivars, and the use of a fungicide is associated with environmental problems. To control the disease without sacrificing the environment, we screened 16 endophytic bacteria, which were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 57 publications
4
21
0
1
Order By: Relevance
“…Antioxidant enzymes (SOD, CAT, and POD) are able to effectively scavenge free radicals and reduce the concentration of reactive oxygen species to alleviate the physiological toxicity of heavy metals to cells. In this study, the activities of CAT, POD, and SOD in the six Cg mycelia were increased under Cd treatment, and the abundance of SOD and CAT in the tolerant strains were higher than those in the sensitive strains ( Figure 2 ), which was consistent with previous research [ 63 ]. Lepista sordida displayed a significant increase in activity of antioxidant enzymes (SOD, POD, and CAT) under Cd and Cu treatment [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Antioxidant enzymes (SOD, CAT, and POD) are able to effectively scavenge free radicals and reduce the concentration of reactive oxygen species to alleviate the physiological toxicity of heavy metals to cells. In this study, the activities of CAT, POD, and SOD in the six Cg mycelia were increased under Cd treatment, and the abundance of SOD and CAT in the tolerant strains were higher than those in the sensitive strains ( Figure 2 ), which was consistent with previous research [ 63 ]. Lepista sordida displayed a significant increase in activity of antioxidant enzymes (SOD, POD, and CAT) under Cd and Cu treatment [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Zheng et al (2017) reported that A. alternata could parasitize Pst, which could be useful in the biological control of wheat yellow rust. Bacillus megaterium 6A Esmail et al Egyptian Journal of Biological Pest Control (2022) 32:116 and Paenibacillus xylanexedens 7A were also shown to greatly suppress the disease severity of wheat yellow rust (Kiani et al 2021). Both antagonistic fungi, tested in this study, improved grain yield components in terms of the number of kernels/spike and 1000-kernel weight.…”
Section: Discussionsupporting
confidence: 50%
“…We studied the morphology of this hyperparasitic fungus, obtained ITS sequences, and built a phylogeny using the NJ method in MEGA10. The molecular data indicated that this fungus belonged to the genus Simplicillium , and the identification of this fungus as S. lanosoniveum had 99% bootstrap support [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%